2015
DOI: 10.1177/0959683615591350
|View full text |Cite
|
Sign up to set email alerts
|

Paleoecological perspectives on landscape history and anthropogenic impacts at Uivak Point, Labrador, since AD 1400

Abstract: Archaeological and paleoecological investigations were undertaken at Uivak Point (HjCl-09 located in Okak Bay, Labrador), a site that consists of a winter village comprising the ruins of nine sod houses and a number of tent ring, cache, and other structures. The site was occupied during the late 18th to early 19th centuries, although the immediate area has been used by many cultural groups spanning from Labrador’s early prehistory into the 20th century. Between ca. 3030 and ca. 710 cal. yr BP, cold and dry cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…Many studies have shown that palaeoenvironmental studies can supplement or offer a new dimension to the chronology constructed by archaeological data (Gauthier et al 2010;Lemieux et al 2011;Massa et al 2012;Roy et al 2012Roy et al , 2015. In our study, palaeoenvironmental records from archaeological sites (and their immediate vicinity) helped us to identify changes in the landscape and land use by identifying traces left by humans since the occupation of Svalbarðstunga.…”
Section: Changes In Vegetation Linked To Anthropogenic Activities Andmentioning
confidence: 85%
See 1 more Smart Citation
“…Many studies have shown that palaeoenvironmental studies can supplement or offer a new dimension to the chronology constructed by archaeological data (Gauthier et al 2010;Lemieux et al 2011;Massa et al 2012;Roy et al 2012Roy et al , 2015. In our study, palaeoenvironmental records from archaeological sites (and their immediate vicinity) helped us to identify changes in the landscape and land use by identifying traces left by humans since the occupation of Svalbarðstunga.…”
Section: Changes In Vegetation Linked To Anthropogenic Activities Andmentioning
confidence: 85%
“…; Roy et al . , ). In our study, palaeoenvironmental records from archaeological sites (and their immediate vicinity) helped us to identify changes in the landscape and land use by identifying traces left by humans since the occupation of Svalbarðstunga.…”
Section: Discussionmentioning
confidence: 99%
“…Houses 1 and 2 at the Oakes Bay 1 archaeological site were situated on sandy marine terraces rising between 5 and 7 m while House 7 of the Uivak Point archaeological site was established on a sandy slope between two boggy terraces at elevations of 8 and 11 m above sea level, respectively (Unit U0) (Roy, Bhiry, & Woollett, ; Roy, Woollett, & Bhiry, ). Lithorelic minerals (e.g., quartz, feldspars, amphiboles, and opaque minerals), which had become encrusted into the archaeological sediments (in Units 1 and 2), came from these sandy terraces.…”
Section: Discussionmentioning
confidence: 99%
“…Palynological research has revealed a restricted suite of microfossils that appear to reflect human impact arising from the activity of these cultures (e.g. Böcher and Fredskild 1993;Roy et al 2015;Ledger 2017). Key amongst these appear to be the increased visibility of certain herbaceous taxa (e.g.…”
Section: Introductionmentioning
confidence: 99%